Conversion in Constantine the Great - Chadwick, Henry (Studies in church history, 1978)
The study of church history, in a degree perhaps unparalleled among the various branches of historical study, combines both the analysis of flux and change and also the continuities and constants that somehow remain through the vicissitudes and disasters of human history. Without needing to have any prefabricated pattern imposed upon it, in Marxist or other style, church history discloses startling continuities, so that to talk about Constantine or Origen or Augustine is somehow not to indulge in antiquarianism but to be talking about issues which (despite vast changes in the intellectual framework within which the debate proceeds) remain alive for the living community of the church now. The sweat drips from our brows as we make die effort to preserve impartiality and detachment. My subject is Constantine’s conversion and the shift that this brought to the intellectual and religious history of Europe. If we put the story back into its historical context and try to look at it with the eyes of a contemporary, the shift may not seem exactly the kind of shift that at first the modern historian thinks he sees.